نظامُ الشركاتِ الجديد وعهد الحوكمةٍ أداة لرفع مستوى أداء المؤسسات الاقتصادية –دراسة تحليلية للمؤسسات الوطنية - mourad, Saouli (Finance and Business Economies Review, 2017)
Is it difficult in this quick reading to control all the amendments added by the system of corporate governance, but it can be noted that it is distinguished from the previous being more aware of the importance of protecting the property of institutions and thus achieve economic development. Many national Algerian institution have taken the initiative to implement and activate governance mechanisms. This system is a means to be followed to ensure the accuracy and improvement of the performance of economic institutions in order to achieve better performance levels to create value and improve the quality of auditing in the institution. To study this concept and analyze it on national institutions and set specific criteria in order to upgrade their economic institutions to the level of outstanding global performance